The transplant of cardiac cells and myoblast skeletal cells in myocardial infarction - Souza,Luiz César Guarita (2002)
OBJECTIVE: To analyze the functional results of adult skeletal muscle cell and cardiac cell transplantations in the hearts of rats that have suffered an infarct. METHOD: An infarct of the anterolateral wall of the left ventricle was provoked, by left lateral thoracotomy and posterior legation of the left coronary artery. After five days the animals were submitted to a transthoracic echocardiography to evaluate the systolic (LVFSV) and diastolic volumes (LVFDV) of the left ventricle and the left ventricle ejection fraction (LVEF). After that, the animals were divided in three groups: 1) control (n=10), 2) adult cardiac cells (n=8) and 3) adult skeletal muscle cells (n=8). Seven days after the myocardium infarct, all the animals were operated on again by median sternotomy, identifying the region with fibrosis and conducting the injection of 0.15 ml of a culture in group I, 8.5x10(6)/0.15 ml, of heterologous skeletal muscle cells in group III, and 8.5x10(6)/0.15 ml of heterologous adult cardiac cells in group II. All animals received cyclosporin (15mg/kg/day). After two months, an echocardiography was conducted on all mice, assessing the same parameters. RESULTS: Two months after transplantation, group I presented a decrease in the LVEF (48.18% + 9.95% vs. 33.25% + 12.41% p=0.0003), with an increase of the LVFSV and the LVFDV (0.308 ml + 0.072 ml vs. 0.536 ml + 0.228 ml p=0.0026 and 0.597 ml + 0.098 ml vs. 0.776 ml + 0.187 ml p=0.0540, respectively). In group II, there was an stabilization of the LVEF (42.48% + 7.83% vs. 41.31% + 8,46% p=0.4968, respectively) an increase in the LVFDV and LVFSV (0.602 ml + 0.203 ml vs. 0.771 ml + 0.110 ml p=0.0711 and 0.358 ml vs. 0.450 ml p=0.0400, respectively). Group III presented an increase on the LVEF, LVFSV and LVFDV (40% + 5.69% vs. 47.35% + 6.89% p=0.0142, 0.643 ml + 0.103 vs. 0.931 ml + 0.226 p=0.0026 and 0.388 ml + 0.082 vs. 0.491 ml + 0.149 ml p=0.0557, respectively). CONCLUSION: Two months after cell transplantation, there was a significant improvement in the LVEF in group III, when compared to group I, and there was a preservation of the ventricular contractility and a stabilization of LVEF in group II.